Risk factors associated with the professional performance of civil servants with impairment - Anjos, Cláudia (2011)
Apresentação realizada na "8th Conference of European Academy of Occupational Health Psychology", que decorreu em Valência, Espanha, de 12 a 14 novembro de 2008